Transformasi Nilai-Nilai Al-Islam dan Kemuhammadiyahan di Era Digital - Abdul Hafiz; Ridwan Ridwan; Aryati Eka Saputri; Saifullah Saifullah (Universitas Islam Negeri Sumatera Utara Medan, 2026)
This study aims to analyze the transformation of Islamic and Muhammadiyah values (AIK) in the digital era, particularly among students at the University of Muhammadiyah Mataram. The phenomenon of digitalization of Islamic learning and preaching has driven fundamental changes in the way students understand, internalize, and express Islamic values. This study uses a qualitative approach with in-depth interviews, participant observation, and digital documentation studies. Data analysis was conducted thematically through the stages of reduction, coding, categorization, and interpretation with the help of qualitative analysis software. The results of the study show four main themes that describe the dynamics of the internalization of AIK values, namely: (1) AIK as the ideological identity of Muhammadiyah students; (2) digital media as a means of preaching and spiritual learning; (3) challenges of ethics and the quality of AIK content in cyberspace; and (4) the need to develop a digital-based AIK development model that is adaptive to the character of the younger generation. These four themes show that AIK values are not only learned cognitively, but also lived and represented through student behavior and interactions in the digital space. These findings emphasize the importance of strengthening the interactive, inspiring, and collaborative AIK learning model to shape the Islamic character of Generation Z amidst the digital transformation.